2007
DOI: 10.1149/1.2737629
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and Thermal ALD of Al[sub 2]O[sub 3] in a Commercial 200 mm ALD Reactor

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

37
274
3
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 266 publications
(316 citation statements)
references
References 31 publications
37
274
3
2
Order By: Relevance
“…From such differential spectra, it is concluded that -OH groups were incorporated in the Al 2 O 3 bulk with the amount of -OH incorporated increasing when going to lower deposition temperatures. This observation is in line with previous reports, 5,9,14 as well as with the compositional data of Al 2 O 3 films deposited in the temperature range studied, i.e., x = ͓O͔ / ͓Al͔ = 1.6 with ϳ4 at. % H at 150°C, x = 1.7 with ϳ7 at.…”
supporting
confidence: 93%
See 3 more Smart Citations
“…From such differential spectra, it is concluded that -OH groups were incorporated in the Al 2 O 3 bulk with the amount of -OH incorporated increasing when going to lower deposition temperatures. This observation is in line with previous reports, 5,9,14 as well as with the compositional data of Al 2 O 3 films deposited in the temperature range studied, i.e., x = ͓O͔ / ͓Al͔ = 1.6 with ϳ4 at. % H at 150°C, x = 1.7 with ϳ7 at.…”
supporting
confidence: 93%
“…1 for H 2 O, 2,9-13 O 3 , 2,13 and O 2 plasma. 9 For temperatures Ͼ100°C, the growth per cycle of Al 2 O 3 monotonically decreases with increasing deposition temperature for all three oxidant sources and the differences are relatively small. Only below 100°C, the growth per cycle significantly differs which has been attributed to difficulties to achieve saturation when dosing H 2 O.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…More details on the preparation of the AI 203 films and their analysis, demonstrating for example a atomic composition of [O]/[AI]=1 .5, a H-content of 2 at.% and a refractive index of 1.62 at 2 eV, can be found in Ref. 20. High resolution transmission electron microscopy (HR-TEM) images, such as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%